2021
DOI: 10.1016/j.joen.2021.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Aerosols Generated during Endodontic Treatment: A Special Concern during the Coronavirus Disease 2019 Pandemic

Abstract: Aims (1) To investigate aerosolized microorganisms generated during endodontic emergencies and non—surgical root canal therapy (NSRCT); (2) To assess how far airborne microbial spread; and (3) To verify the spatial distribution of airborne microbial spread. Methods A total of 45 endodontic procedures were sampled, including full pulpotomy (n=15), pulpectomy (n=15), and NSRCT (n=15). Samples were collected during room resting (s1) and after the treatment (s2). The passiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 33 publications
2
19
1
Order By: Relevance
“…Studies have shown that using rubber dams during operations reduced colony counts by 82.7% (lamp-side sampling) and 83.9% (chest-side sampling) ( 95 ). Most studies have formed a broad consensus that rubber dams effectively reduced splatter transmission by 33% and reduced surface bacterial contamination by 80–99% during aerosol generation ( 96 ). Therefore, the use of rubber dams, where possible, can be effective in reducing aerosol formation during clinical operations.…”
Section: Strengthen Infection Control and Prevention In The Dental Clinic Environmentmentioning
confidence: 99%
“…Studies have shown that using rubber dams during operations reduced colony counts by 82.7% (lamp-side sampling) and 83.9% (chest-side sampling) ( 95 ). Most studies have formed a broad consensus that rubber dams effectively reduced splatter transmission by 33% and reduced surface bacterial contamination by 80–99% during aerosol generation ( 96 ). Therefore, the use of rubber dams, where possible, can be effective in reducing aerosol formation during clinical operations.…”
Section: Strengthen Infection Control and Prevention In The Dental Clinic Environmentmentioning
confidence: 99%
“…In particular, the dental community faced unique challenges, leading to the development of treatment strategies changes to reduce the risks of virus transmission to patients/dental practitioners ( Bahador et al, 2021 ). In endodontics, a shift towards minimally invasive endodontic procedures was suggested over more invasive modalities highlighting a new role for these therapies in light of the COVID-19 pandemic ( Azim et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aerosols generated during dental procedures have become a target of concern and discussion 1 , 2 , since are vectors of infective agents including bacteria, yeasts, filamentous fungi, and viruses 3 7 . So, aerosol particles show high potential for contamination that not only reach the dental care professional and patients, but also all exposed surfaces of the dental unit and the operatory environment 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…So, aerosol particles show high potential for contamination that not only reach the dental care professional and patients, but also all exposed surfaces of the dental unit and the operatory environment 6 , 7 . Not different, there is a risk of transmission of acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which results in the COVID-19 disease, in dental practice carried by aerosol particles 2 , 3 from blood, saliva, and other body fluids exposure of symptomatic and asymptomatic patients, combined with instruments that generate aerosols 8 .…”
Section: Introductionmentioning
confidence: 99%